Class Teacher Students’ Beliefs about Teaching, Ability and Research Skills - Saariranta, Petra (fi=Turun yliopisto|en=University of Turku|, 2017)
The aim of teacher education is to train high level experts of education who possess a wide range of theoretical-methodological skills. Prior research has shown that students’ beliefs strongly influence what knowledge they deem as important. This study examined class teacher students’ beliefs about the skills needed in teaching and the ability of teacher education to equip students with those skills. Students’ beliefs about teaching knowledge and teaching ability were studied. First Year and Master’s Degree class teacher students answered a questionnaire. Belief differences were found between the two groups. Master’s Degree students rated seven research skills as statistically significantly more important in the teaching profession than did the First Year students. Master’s Degree students also evaluated the skill equipping ability of teacher education to be weaker than the First Year students did in terms of eight research skills. Both groups of students believed practical skills to be most important in teaching, but theoretical knowledge and a theoretical understanding of teaching practices were also deemed important. Master’s Degree students had statistically significantly stronger beliefs about the importance of theoretical knowledge. Both groups displayed quite a wide spectrum of teaching ability beliefs i.e. is teaching a learned, an innate or both a learned and innate skill. Master’s Degree students had stronger beliefs about learned teaching ability and innate teaching ability. Three main student profiles emerged from the study: Advanced, Practicals and Moderates. Advanced students had strong teaching knowledge beliefs. Advanced students were divided into two subgroups based on teaching ability beliefs. Advanced (diverse abilities) students had a diverse, broad spectrum of teaching ability beliefs. Advanced (narrow abilities) students had more narrow teaching ability beliefs and they believed very strongly that teaching is an innate skill. Practicals had strong beliefs about the importance of practical skills, but weak beliefs about the importance of theoretical knowledge. The Practicals (diverse abilities) students had a diverse, broad spectrum of teaching ability beliefs, whilst the Practicals (narrow abilities) students had strong beliefs about innate teaching ability, but weaker learned and both innate and learned ability beliefs. Moderates had both moderate teaching knowledge and teaching ability beliefs in comparison to the two other main student profiles. The teaching knowledge and ability beliefs of those with and without paid teaching experience were compared, but no significant differences between the two groups were found.